Respostas

  • Usuário do Brainly
2014-07-27T21:56:17-03:00
 \left \{ {{x+6y=3} \atop {xy=-9}} \right.

isola

x=3-6y

subst/
y(3-6y)=-9

3y-6y²=-9
-6y²+3y+9=0  (:-3)
2y²-y-3=0
Δ=1+24
Δ=25
√Δ=√25=5

y'= \frac{1+5}{4} = \frac{6}{4} = \frac{3}{2}

y"= \frac{1-5}{4} = \frac{-4}{4} =-1

como x=3-6y      
          p/ y=3/2      ou      p/ y=-1
       x=3-6(3/2)                x=3-6(-1)
       x=3-9                        x=3+6

       x=-6                          x=9
S={(-6,3/2)} ou {(9,-1)}
1 1 1
2014-07-27T23:50:42-03:00
X=3-6y
xy=-9
(3-6y)y=-9
3y-6y²=-9
-9-3y+6y²=0
6y²-3y-9=0
aplicando a formula de baskara
x=-b+-√b²-4ac/2
x=3+-√3²-4.6.(-9)/2.6
x=3+-√9+216/12
x=3+-√225/12
x=3+-15/12
x1=3+15/2
x1=18/12
x1=3/2
x2=3-15/12
x2=-12/12
x2=-1